مغربی اخلاقی اقدار کے مسلم معاشرے پر اثرات: Effects of Western Moral Values on Muslim Society - Muhammad AbuBakar; Nabvi Shaheen (International Research Journal of Arabic and Islamic Studies, 2023)
The dominance of liberal democracy and capitalist civilization on the world stage has exposed the godless culture of the West to the world through education and especially the mass media. Unfortunately, Pakistan too could not be safe from it. Those few people who were putting up defensive fronts against this cultural invasion are getting weaker in front of the modern trends of education. These few members of the society can resist in their individual lives and families, but it does not seem possible to stop the growing steps of liberalism in the streets, markets, neighborhoods, cultural centers and educational institutions, even knowingly or unknowingly the standards of the West. The standards of the society are becoming the result of this trend of modernity that what meets the standards of the West is considered to be proud. Those that do not meet this standard are rejected. Although the claim to be free continues with full force in its place, but in reality mental slavery and subjugation is a concrete reality. The paper presents an analysis of the impact of Western values on Muslim society.